Estudo etnobotânico, químico e avaliação do potencial efeito biológico de Kielmeyera coriacea (Calophyllaceae) - (:unkn) unknown (Universidade Federal de Goiás, 2015)
Brazil has the greatest biodiversity in the world, and the plants are major sources of active molecules, having wide structural diversity. Among the domains found in Brazil, the Cerrado is a great source of medicinal plants with biological activities, and promising for the identifi-cation of bioactive molecules. In this context, studies on species of the Cerrado, can signifi-cantly contribute to the development and preservation of this biome. The species Kielmeyera coriacea (Calopyllaceae) is popularly known as pau-santo, being native to the Brazilian cen-tral plateau region. It is used in popular medicine, mainly for gastritis, anemia and leukemia, as reported in ethnobotanical interviews conducted in this study. The chemical study of K. coriacea leaves afforded the substances lupeol, lupenone, β-amyrin, cis and trans-p-coumaric acid and flavonoid quercetin, which was evaluated against the cathepsin V (CatV) and has a high inhibitory potential, had its IC50 assessed, with a value of 2.2 μM. The leaves extract (LE) and fractions originating from the liquid-liquid partition K. coriacea were also tested against cathepsins, and the LE showed the most satisfactory results against CatV, inhibiting the activity by 98%; LE was also tested against the ulcerogenic action, with concentrations of 200 and 300 mg.kg-1, and showed significant inhibition of ulcerative lesions. For antimicrobi-al evaluation, LE showed antimicrobial activity against the fungi Candida albicans, C. tropi-calis and C. glabrata (MIC of 31,25 μg/mL, 62,5 μg/mL e 7,81 μg/mL). Therefore, this re-search made possible the correlation ethnobotanical and scientific data, and contributed with relevant information of chemical-biological character of K. coriacea.
Study ethnobotanical, chemical and biological evaluation of potential effect kielmeyera coriacea (Calophyllaceae)
Keywords: Kielmeyera coriacea; Estudo etnobotânico; Estudo químico; Ensaios biológicos; Ethnobotanical study; Study chemical; Biological assays; CIENCIAS EXATAS E DA TERRA::QUIMICA